2013
DOI: 10.1590/s0036-46652013000300001
|View full text |Cite
|
Sign up to set email alerts
|

Variability in Galactomannan detection by platelia Aspergillus EIA™ according to the Aspergillus species

Abstract: SUMMARYHere we investigate the extent to which different Aspergillus species release galactomannan (GM) in vitro. Marked variability was observed in GM reactivity between and within Aspergillus species, with A. terreus strains showing the highest GM indexes. The in vivo significance of these findings remains to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…Since Aspergillus hyphae release far more GM than Aspergillus conidia, strain-related differences in germination could explain these findings 11,12 . Differences in GM release have already been described between and within Aspergillus species, including in the same strains of A. fumigatus used in our study 13,14 .…”
Section: Gm Indexsupporting
confidence: 63%
“…Since Aspergillus hyphae release far more GM than Aspergillus conidia, strain-related differences in germination could explain these findings 11,12 . Differences in GM release have already been described between and within Aspergillus species, including in the same strains of A. fumigatus used in our study 13,14 .…”
Section: Gm Indexsupporting
confidence: 63%
“…However, restriction to a specific species decreases the risk of PCR positivity from environmental non- fumigatus DNA, especially if high C q are to be considered ( Alanio and Bretagne, 2014 ), although contamination with A. fumigatus DNA cannot be completely excluded ( Harrison et al, 2010 ; Millon et al, 2010 ). Moreover, since all the Aspergillus species do not equally produced GM in the same quantity ( Xavier et al, 2013 ), quantitative comparison between GM and circulating DNA would have been biased if a non- A. fumigatus specific PCR had been used.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, none of the previous studies reported a twofold mean of the GM index in IA patients with A. fumigatus in comparison to IA patients with A. flavus. Xavier et al [53] in an in vitro study found that the quantity of scattered GM varies according to the species of Aspergillus. They demonstrated that among different species of Aspergillus, Aspergillus terreus has the maximum GM index, closely followed by A. fumigatus in comparison to Aspergillus niger and A. flavus [53].…”
Section: Discussionmentioning
confidence: 98%
“…Xavier et al [53] in an in vitro study found that the quantity of scattered GM varies according to the species of Aspergillus. They demonstrated that among different species of Aspergillus, Aspergillus terreus has the maximum GM index, closely followed by A. fumigatus in comparison to Aspergillus niger and A. flavus [53]. Another study showed a higher secretion of GM by A. niger and A. flavus in comparison to A. fumigatus [54].…”
Section: Discussionmentioning
confidence: 98%